2022
DOI: 10.1002/adbi.202200033
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells in Peripheral Cancers: Bystanders or Promoters?

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adbi.202200033.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…SC have been recently shown to play a role in maintenance of the immunosuppressive tumor microenvironment by chemoattraction and polarization of myeloid regulatory cells and upregulating their ability to reduce activity of T cells [ 20 , 22 , 34 ]. SC were also reported to be capable of directly stimulating malignant cell motility and formation of metastases [ 21 , 35 , 36 ]. However, SC-derived factors affecting myeloid regulatory cells have not been yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…SC have been recently shown to play a role in maintenance of the immunosuppressive tumor microenvironment by chemoattraction and polarization of myeloid regulatory cells and upregulating their ability to reduce activity of T cells [ 20 , 22 , 34 ]. SC were also reported to be capable of directly stimulating malignant cell motility and formation of metastases [ 21 , 35 , 36 ]. However, SC-derived factors affecting myeloid regulatory cells have not been yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…Our recognition of the relevance of SC activity and lung cancer is still in its infancy although the important role of SCs in other cancer types has already been demonstrated ( Deborde and Wong, 2017 ; Martyn et al, 2019 ; Shurin et al, 2021 ; Deborde and Wong, 2022 ; Yurteri et al, 2022 ). Analysis of SC biology in prostate, pancreatic, cervical, oral, colon tumors, melanoma, and other cancer types revealed their involvement in perineural invasion, cancer pain, and tumor cell proliferation, dispersion, invasion, and metastasizing ( Demir et al, 2014 ; Deborde et al, 2016 ; Shan et al, 2016 ; Shurin et al, 2019 ; Huang et al, 2020 ; Salvo et al, 2021 ; Santi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also observed that advanced stages of lung cancer exhibited the highest levels of SC detection ( Zhou et al, 2019 ). Although the identification of SCs in different solid tumors and their role in the development and metastasis formation in different types of cancer have been repeatedly reported and reviewed ( Bunimovich et al, 2017 ; Deborde and Wong, 2022 ; Sun et al, 2022 ; Yurteri et al, 2022 ; Xue et al, 2023 ), data describing the functional significance of tumor-associated SCs (TA-SCs) in lung cancer are scarce ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a dynamic communication between the nerves and PDAC cells further facilitates immune escape, tumor growth, and metastasis. SCs are believed to possess the potential to drive tumorigenesis, produce signals to promote cancer invasion, and reshape the ECM [ 40 ]. From a clinical perspective, the development of novel therapies targeting the modification of SCs’ repair phenotype holds promise for mitigating perineural invasion in PDAC.…”
Section: Discussionmentioning
confidence: 99%